Analiza przestrzenna profilu społecznego województw z wykorzystaniem programu R - Sej-Kolasa, Małgorzata; Sztemberg-Lewandowska, Mirosława (Spatial Analysis of the Social Profiles of Provinces with the Use of the R Software, 2009)
A spatial analysis of data makes it possible to define the similarities and differences among regions. The aim of this study was to identify the determiners of the social situation in Poland. Another important aspect was a comparative analysis of the determiner strengths in each region. The analysis covered 50 indices describing the social profile of every Polish province, including the sizes and levels of population, labour market, housing, education, culture and healthcare. Decomposition of the data covered by the set of indices (random variables) was performed through factor analysis. The spatial visualisation of data was performed with the R software. The data was plotted against choropleth maps of the administrative division of Poland. The basis of map creation was a shapefile generated with GTS-type software.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 176-184